Characterisation of zinc‐chelating peptides derived from scallop (Patinopecten yessoensis) mantle and their intestinal transport in everted rat sacs. (26th March 2023) - Liu, Xiaoyang; Sun, Jiatong; Li, Yue; Yu, Xuening; Yin, Fawen; Li, Deyang; Jiang, Pengfei; Nakamura, Yoshimasa; Zhou, Dayong
Summary: Recently, food‐derived peptides were frequently studied and used as metal ion chelator against negative effects of trace element absorption induced by various human gastrointestinal environments. In this study, the scallop mantle hydrolysates (SMHs) were produced and characterised to study their intestinal promotion of zinc absorption. During production of hydrolysates, the results of degree of hydrolysis (DH) and proteins solubility suggested that the alcalase was suitable for the production of peptides from scallop mantle proteins where the chelating conditions were settled (30 °C, 10 min and 3 mg mL −1 ). The molecular distribution of SMH was mainly 1–5 kDa and chelation of zinc with SMH (involved in carboxyl and amine group of SMH) triggered no significant alteration on the secondary structure of SMH. Zinc morphologically altered the surface structures of SMH. Moreover, SMH could successfully carry and transport zinc while the fluorescence staining indicated free zinc accumulated inside the tissue of everted rat sacs. Finally, several representative transported peptides (intact or cleaved) were identified, such as FTGEPGPSGPT, AINDPFIDL and ALPHAILRI. This study provided a theoretical basis for the investigation of absorption of marine animal‐derived peptides as zinc carriers. Abstract : Scallop metal hydrolysates (SMHs) exhibited well zinc‐chelating ability. SMH‐Zn transported across membrane of everted rat gut sacs. SMH‐Zn might release the zinc ions inside the membrane cell. Several intact and cleaved transported peptides were identified.